Development of teacher innovation in teaching accounting subject through implementation of professional learning community - Ahmad Jalaludin, Afaf; Abdul Kadir, Suhaida; Abdullah, Arnida; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2022)
Critical thinking is important because critical thinking is a generic skill required by employers to produce students who can compete in today's global economic market. Teacher quality is the main focus in education management because the relationship between student achievement is closely related to the teacher's ability to manage student-based learning. Among the methods for teachers to be involved in professional development that leads to increased student learning is the Professional Learning Community (PLC). The purpose of this article is to examine how the implementation of PLC leads to the development of innovation among Accounting teachers. A total of seven Accounting teachers who teach Forms 4 and 5 in seven schools in southern Malaysia were selected as study participants using the purposive sampling. Three data collection techniques were used to obtain rich data, namely semi-structured interview, document analysis, and audio and visual material analysis. The validity and reliability of the findings of this study is ensured through triangulation, member checking, peer review, audit trail, and a prolonged and adequate engagement in the study. The findings of the study are categorized into 3 themes, namely Sharing Best Practices, Collective Focus on Student Learning, and Collaborative.